A Study Of Systemic Variation And Frequency Of Modified Idiom In Forbes Asia And The Economist - Payo, Laila (2020)
Modified idiom or idiom with variation pose many semantic problems especially to non-native speakers of English language. It appeared that many non-native speakers of English language often find themselves loss in understanding the full meaning of the message while reading the context with modified idiom, and one of the reason of misunderstanding the message is the lack of familiarity of modified idiom. Non-native speakers of English language are not familiar with the change of idiom’s form and then, face the error in understanding the messages. Therefore, this study is designed to investigate types and the frequency of systemic variation of modified idiom in the context of case study, includes Forbes Asia and The Economist